Assessing writing of descriptive text using portfolio assessment plan as formative assessment - Mustikareni, Dyah (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
Descriptive text is one of the genres which is included in the English Curriculum for the Tenth Graders of Senior High schools in Indonesia. The identification of the descriptive text is usually the main idea of the paragraph or called a general statement, and the description of the descriptive text is about the explanation of the general statement or main idea or supporting details to the general statement. Portfolio Assessment Plan (PAP) is one of formative assessment that becomes an alternative tool for assessing in English language teaching classrooms, including writing skills. The portfolio procedures comprise the collection, selection, self-assessment, reflection, and delayed evaluation and are embedded within multiple feedback sources. Possible challenges come up in implementing this PAP, such as the students could run of time before they finish the work, searching the information from Google could distract students, and similar writing could happen between students. To address the possible challenges above, there are some solutions. First, teachers have to notice the ‘insufficient learner engagement. Second, reminding them to use their time wisely by searching the useful information only is needed. Third, it needs the teachers’ management when find there is the same topic used by the students.